The Sechabaism Scholarship of Humanity to African Research: Reflections from the Life and Works of Professor Sechaba Mahlomaholo - Bekithemba Dube (Journal of Education and Learning Technology)
This article is a reflection and proposes a theory based on the work and life of Sechaba Mahlomaholo. To consolidate points in this paper, the Sechabaism scholarship of humanity is used as an embodiment of his life and work in South African Higher Education and beyond. Those who knew and read his works would agree that his scholarship did not diminish his humanity through which people can be great scholars and be able to create a convivial community that emancipates people facing systematic injustice, xenophobia, and racial segregation among many others. His scholarship was always open to all disfranchised people excluded from higher education based on race and nationality. This act of conviviality was optimised in his movement known as Sustainable Learning Environments (SULE). In this paper, I deduce five critical elements which are Civic Research, Social Justice, Positive Change Research and Respectful Research which premise the Sechabaism scholarship of humanity. I argue in this paper that the Sechabaism scholarship of humanity presents a new outlook of African scholarship that has an impetus to contribute to social transformation and improved relations in higher education.